Innovation Development Strategy of Entrepreneurial Skills Education Program in Parepare - Hasdiansyah, Andi; Ridwan, Ihwan; Achmad, Ilmar A; Artati, Yuli (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Innovation in the Entrepreneurial Skills Education (PKW) program is urgently needed. For this reason, an appropriate strategy is required so that the PKW program can align with the times. This study aims to find a strategy model for developing innovation in the PKW program organized by PKBM Sipatuwo Deceng in Parepare City for 2020–2022. This study used a qualitative research method with a case study design. In collecting data, 10 participants were interviewed intensively and in-depth for approximately 3 months, offline and online. The collected data were analyzed using interactive analysis techniques developed by Miles & Huberman. Based on the review and analysis, this study revealed several findings. First, the PKW program was developed by mobilizing community participation through social action during the COVID-19 pandemic. Second, the strategy for developing the PKW program innovation is based on a gradual cycle. Starting with project discussions, case studies, feedback, and forming working groups. Third, the weaknesses were identified, recommending that financial literacy and strengthening the character of participants become essential parts of future PKW programs. Overall, the PKW program development strategy implemented by PKBM Siaptuwo Deceng was quite successful and had a real impact.